Analisis Variabel-Variabel Risiko pada Pelaksanaan Proyek Konstruksi Jalan - Hidayati, Rahmi; Natalia, Monika; Adibroto, Fauna; Mafriyal, Mafriyal; yurisman, yurisman; Saskia, Rizkina (Jurnal Ilmiah Rekayasa Sipil, 2017)
This research aims to identify the risk variables that ever occurred while executing of road construction project. In addition, it is to identify how significant and how big the influence of risk variables to the articulation of project execution processes of a road construction project, based on questionnaire that distributed to 30 questionnaires who are project managers and site managers on contractors of road construction project. From the research data, there were identified 14 risk variables with 84 risk sub-variables on execution of road construction project. Those 14 risk variables were natural, social, politic, economic, law, occupational safety and health, managerial, technical, cultural, logistic, condition around construction site, design and technology, labor, and contractual variables. From the data analysis by using SPSS version 16, obtained there were 14 risk sub-variables which became the most influential sub-variables (indicators) to the road construction project. All sub-variables on the questionnaire are valid and reliable. The results of this research is expected to be considered for all parties involved in the construction project to pay more attention to risk variables during the execution of road construction project.